Claude Monet : the revised catalogue raisonné : pastels - Wildenstein Plattner Institute (2023)
This online presentation of the pastels by Claude Monet marks the first installment of the WPI’s long-term project to revise Daniel Wildenstein’s original catalogue raisonné of the artist’s entire oeuvre.